RESEPSI AL-QUR’AN TENTANG JAMINAN RIZKI SETELAH MENIKAH PADA JAMAAH MAJELIS TAKLIM DAN DZIKIR AL-MUFLIHIN - Abidin, Achmad Azis; Ariyanto, Nurul (Journal of Islamic Studies and Humanities, 2021)
This article analyzed the understanding of the group of Majelis Taklim and Dzikir al-Muflihin in Cepu Village, Cepu Subdistric, Blora Distric toward the holy Qur’an verses wich explains about the guarantee of sustenance after wedding. It used a field research paradigm with the Living Qur’an thematically approach that focuses on the holy Qur’an verses about the guarantee of sustenance after wedding. Data acquisition was done in two ways, by observation and interview. The conclusion was that the group of Majelis Taklim and Dzikir al-Muflihin understood that the guarantee of sustenance referred in the holy Qur’an verses includes: pleasure of the heart; the ability to strive; steady work, unexpected sustenance; and pious descendants.